2017
DOI: 10.3390/insects8020044
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among the Predatory Midge Aphidoletes aphidimyza (Diptera: Cecidomyiidae), the Fungal Pathogen Metarhizium brunneum (Ascomycota: Hypocreales), and Maize-Infesting Aphids in Greenhouse Mesocosms

Abstract: The generalist entomopathogenic fungus, Metarhizium brunneum, has proved to have great potential as a versatile biological pest control agent. The gall midge Aphidoletes aphidimyza is a specialist predator that occurs naturally in Europe and has been successfully used for aphid suppression. However, the interaction between these two biological control organisms and how it may affect the biological control of aphids awaits further investigation. As part of the EU-supported project INBIOSOIL, this study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Generally speaking, the consequences of microbe-plant-insect interactions are complicated and rely on many factors [ 18 ], especially when considering higher trophic levels (i.e., parasitoids and predators), and potential adverse effects between EF and natural enemies are important to consider [ 19 , 20 ]. Previous studies have shown compatibility between EF and beneficial arthropods [ 21 23 ], but there are also reports of EF causing higher mortality, lower fecundity and reduced longevity in predators and parasitoids, and other studies have shown competition for resources between the two groups of natural enemies [ 24 26 ]. We know that EF may influence the performance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the consequences of microbe-plant-insect interactions are complicated and rely on many factors [ 18 ], especially when considering higher trophic levels (i.e., parasitoids and predators), and potential adverse effects between EF and natural enemies are important to consider [ 19 , 20 ]. Previous studies have shown compatibility between EF and beneficial arthropods [ 21 23 ], but there are also reports of EF causing higher mortality, lower fecundity and reduced longevity in predators and parasitoids, and other studies have shown competition for resources between the two groups of natural enemies [ 24 26 ]. We know that EF may influence the performance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Larvae of Allograpta oblicua (Say) (Syrphidae) fed on the aphid, although Gamboa et al (2016) found Chrysoperla carnea (Stephens) (Chrysopidae) the main predator of In this study, 25 adults and 14 larvae of Aphidoletes spp (Diptera: Cecidomyiidae) were preying on Aphis gossipii in Lepidium virginicum (Table 3). The larva of the fly can consume 50 aphids in 1 day (Campos de Azevedo et al 2017), which shows the potential of the insect to manage aphids in crops. Other Diptera found in smaller numbers were adult Chamaemyiidae (Diptera) (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst those females that emerged, fecundity was not affected by treatment. Our previous greenhouse study showed that the number of A. aphidimyza midges emerging from M. brunneum-treated soil and the number of eggs laid were not affected by fungal presence; however, the number of midges was four times higher in the control than in the treatment at the end of the experiment (Azevedo et al, 2017).…”
Section: Effects Of Exposure To M Brunneum In the Soil On Fitness Atmentioning
confidence: 86%